2021
DOI: 10.13057/biodiv/d220337
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, diversity and antimicrobial resistance of Salmonella enterica and Pseudomonas aeruginosa isolates from spring water in a rural area of northwestern Morocco

Abstract: Abstract. Nassri I, Tahri L, Saidi A, Ameur N, Fekhaoui M. 2021. Prevalence, diversity and antimicrobial resistance of Salmonella enterica and Pseudomonas aeruginosa isolates from spring Water in a rural area of northwestern Morocco. Biodiversitas 22: 1363-1370. The persistence and diversity of serotypes belonging to pathogens in environmental waters including surface and groundwater have been widely documented and that the aquatic environment represents a relatively stable environment for these microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The poultry farming activity developed under the impetus of private investors with sustained growth from the 1960s around the major cities of the Atlantic zone (Sraïri, 2011). The presence of clinically important Salmonella enterica in natural waters follows the same trends as infection in humans and wildlife in the same area, suggesting a common origin of this germ (Nassri et al, 2021).…”
Section: Occurrence Of Salmonella In the Environmentmentioning
confidence: 72%
See 1 more Smart Citation
“…The poultry farming activity developed under the impetus of private investors with sustained growth from the 1960s around the major cities of the Atlantic zone (Sraïri, 2011). The presence of clinically important Salmonella enterica in natural waters follows the same trends as infection in humans and wildlife in the same area, suggesting a common origin of this germ (Nassri et al, 2021).…”
Section: Occurrence Of Salmonella In the Environmentmentioning
confidence: 72%
“…Most of the research work on Salmonella in the environment has been carried out in water environments, such as wells (Lotfi et al, 2020, Nassri et al, 2021, running waterways (Ben Moussa et al, 2014), water from dams (Chahboune et al, 2014), wastewaters (Ait Melloul and Hassani, 1999), and seawater (Setti et al, 2009). However, the complete study by serotyping and the study of antibiotic resistance is generally not carried out or not reported.…”
Section: Occurrence Of Salmonella In the Environmentmentioning
confidence: 99%
“…Furthermore, this resistance profile has been found not only in cosmopolitan isolates but has also in wild isolates obtained from rural areas, whose scenario hypothetically exerts less selective pressure, compared to urban environments. In addition, urban areas are more densely populated and bacteria are highly exposed to sources of contamination of anthropogenic origin (Hafiane et al, 2019, Nassri et al, 2021. This illustrates the inherent intrinsic resistance of P. aeruginosa to antibiotics, which in terms of public health, poses a threat when some strains exhibit wild-type virulence factor phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…For the identification in sediment, a 100 mL of PBS, in which the sediment sample was processed, was filtered. The filtration membrane was transferred to 50 mL of Buffered peptone water (BPW), a Salmonella pre-enrichment broth, and incubated at 36 ± 2 °C for 18 ± 2 h. After incubation, the PBS aliquots were transferred to different broths— the Rappaport–Vassiliadis Soya Peptone Broth (RSV Broth) and the Muller–Kauffmann tetrathionate-novobiocin broth (MKTTn)—and incubated at 41.5 ± 1.0 °C for 24 ± 3 h and at 36 ± 2 °C for 24 ± 3 h, respectively [ 28 , 29 ]. For the Shigella spp.…”
Section: Methodsmentioning
confidence: 99%